The Effectiveness of Rational Emotive Behavior Therapy (REBT) Group Counseling in Enhancing Academic Resilience among Students with Academic Difficulties - Zarisman, Esi; Netrawati, Netrawati (Journal of Educational, Health and Community Psychology, 2025)
Many students struggle to cope with academic pressure, leading them to give up easily when they receive poor grades, face difficult assignments, or experience failure. Over time, these experiences can erode self-confidence and foster self-deprecating beliefs, such as perceiving themselves as “stupid.” This study examined the effectiveness of Rational Emotive Behavior Therapy (REBT) group counseling in enhancing the academic resilience of students with academic difficulties. The research was conducted at SMP Pembangunan Laboratorium UNP with a sample of 20 students. A quantitative approach with a quasi-experimental pretest–posttest control group design was employed. Participants were selected using random sampling, and data were collected using a Likert-type academic resilience scale. Data were analyzed using the Wilcoxon signed-rank test and the Mann–Whitney test. The Wilcoxon signed-rank test indicated a significant increase in academic resilience in the experimental group (Z = −2.81, p = .005) and a significant change in the control group (Z = −2.81, p = .005). Furthermore, the Mann–Whitney test showed a significant difference in posttest academic resilience scores between the experimental and control groups (Z = −3.80, p = .001), demonstrating that REBT group counseling is effective in improving the academic resilience of students with academic difficulties.